AN OBSERVATIONAL PREDCTION OF LAND SUBSIDENCE FOR A GIS-AIDED MONITORING SYSTEM OF GROUNDWATER LEVEL - S. Murakami; K. Yasuhara; N. Mochizuki (Lowland Technology International, 2002)
A simplified method for observational prediction of land subsidence based on settlement versus time records being previously observed at locations of the objective area was proposed in the present paper for use of the geographical information system (GIS). However, no consideration of ground water level (GWL) variations was taken into proposal of the method. The present paper, however, attempts to realize use of this time series analysis. Settlement variations over time predicted using the proposed two methods available for cases with and without consideration of GWL fluctuation were compared with those observed at locations in the objective area. In comparison with a method which ignores GWL fluctuation, better agreement was recognized between predicted and measured settlement versus relations. In particular, it was found that the proposed method succeeds in predicting settlemet acceleration over time during water shortage periods. Results predicted using the proposed method are displayed as a hazard map using the GIS. Based on the GIS application map, a possible monitoring system is presented for groundwater usage optimization.